Finite-time lag projective synchronization of delayed fractional-order quaternion-valued neural networks with parameter uncertainties - Shang, Weiying; Zhang, Weiwei; Zhang, Hai; Zhang, Hongmei; Cao, Jinde; Alsaadi, Fawaz E. (Nonlinear Analysis: Modelling and Control, 2023)
This paper discusses a class issue of finite-time lag projective synchronization (FTLPS) of delayed fractional-order quaternion-valued neural networks (FOQVNNs) with parameter uncertainties, which is solved by a non-decomposition method. Firstly, a new delayed FOQVNNs model with uncertain parameters is designed. Secondly, two types of feedback controller and adaptive controller without sign functions are designed in the quaternion domain. Based on the Lyapunov analysis method, the non-decomposition method is applied to replace the decomposition method that requires complex calculations, combined with some quaternion inequality techniques, to accurately estimate the settling time of FTLPS. Finally, the correctness of the obtained theoretical results is testified by a numerical simulation example.
Keywords: quaternion-valued neural networks; finite-time lag projective synchronization; parameter uncertainties